2019
DOI: 10.3390/brainsci9080183
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor Subtype 5 in Alcohol-Induced Negative Affect

Abstract: Allosteric modulators of metabotropic glutamate 5 receptors (mGlu5 receptors) have been identified as a promising treatment to independently alleviate both negative affective states and ethanol-seeking and intake. However, these conditions are often comorbid and might precipitate one another. Acute and protracted ethanol withdrawal can lead to negative affective states. In turn, these states are primary drivers of alcohol relapse, particularly among women. The current review synthesizes preclinical studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 115 publications
0
11
0
Order By: Relevance
“…At face value, it may seem less likely that mGlu receptor signaling contributed to the IT-specific synaptic adaptations observed in the present studies. Nonetheless, several forms of signaling dependent on mGlu 5 receptors are disrupted following EtOH exposure (Joffe et al, 2018;Kasten et al, 2019), raising the possibility that increased postsynaptic strength in IT neurons may have followed from disrupted mGlu receptor LTD. Relatively mild stress disrupts PFC LTD through specific changes to discrete signaling pathways downstream from mGlu 5 receptors and Homer proteins (Joffe et al, 2017(Joffe et al, , 2019, and IA EtOH exposure may disrupt LTD through similar mechanisms as observed in many other brain regions (Quadir et al, 2016;Szumlinski et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…At face value, it may seem less likely that mGlu receptor signaling contributed to the IT-specific synaptic adaptations observed in the present studies. Nonetheless, several forms of signaling dependent on mGlu 5 receptors are disrupted following EtOH exposure (Joffe et al, 2018;Kasten et al, 2019), raising the possibility that increased postsynaptic strength in IT neurons may have followed from disrupted mGlu receptor LTD. Relatively mild stress disrupts PFC LTD through specific changes to discrete signaling pathways downstream from mGlu 5 receptors and Homer proteins (Joffe et al, 2017(Joffe et al, , 2019, and IA EtOH exposure may disrupt LTD through similar mechanisms as observed in many other brain regions (Quadir et al, 2016;Szumlinski et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be hypothesized that treatment with the mGlu5 receptor PAM during the ethanol withdrawal altered the rats' interoceptive state so that it is different from the state that is typically experienced during ethanol-CPP sessions. Thus, targeting mGlu5 may be useful, for example, for ameliorating anhedonia and dysphoria following the cessation of drug/ethanol intake [46].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recently discovered novel group of biased ligands of mGlu5 PAMs has been found that selectively potentiates the coupling of mGlu5 to G ∝q GTP-binding proteins and subsequently mobilizes intracellular calcium and activates protein kinase C and associated signaling pathways that lead either (via complex kinase cascade and Arc protein) to the internalization of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors [45] or the activation of presynaptic type 1 cannabinoid (CB1) receptors. In turn, the activation of presynaptic CB1 receptors regulates γ-aminobutyric acid (GABA)/glutamate release [46,47]. Taking into account the above data, biased ligands of mGlu5 PAMs might have, being cognitive enhancers, a better safety profile than nonbiased mGlu5 PAMs that induce neurotoxicity associated with increased NMDA receptor currents [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is possible that the results of these studies may have been different if the mGlu5 receptor knockdown surgery occurred after AIE treatment during late adolescence/ early adulthood instead of prior to AIE during early adolescence. Due to the emergence of negative affectivelike behaviors during adolescence 4 , these studies focused on concurrent mGlu5 receptor knockdown and vapor exposure during adolescent development to better capture relevant changes in mGlu5 signaling that may occur through the entirety of adolescence and play a role in alcohol-induced negative affect 26 . In adult male mice, restraint stress enhances GluN2Bmediated signaling in the BNST of mice with an AIE history 25 .…”
Section: Aie Produces Distinct Behavioral Profiles Mediated By Bnst-mmentioning
confidence: 99%
“…Recent work in our lab has demonstrated that this disrupted mGlu1/5-mediated signaling in the BNST is associated with stress-induced anhedonic states in adulthood following AIE that are present in female, but not male, mice 20 . Preclinical studies have consistently implicated mGlu5 receptors in reducing alcohol intake and regulating alcohol-induced negative affect-like behavior across a diverse array of behavioral paradigms, including despair- and anxiety-like behaviors 26 . Further, human postmortem studies show sexually dimorphic mGlu5 receptor expression in individuals with major depressive disorder (MDD) compared to control samples.…”
Section: Introductionmentioning
confidence: 99%